(untitled) (Research, Society and Development, 2022)
Primary Health Care (PHC) is considered the privileged space for the insertion of health education, as it is recognized as the coordinator of care. It provides a practice of comprehensive health care considering its biopsychosocial determinants, promotion, prevention, recovery and rehabilitation actions, in an interprofessional way, through networking and integrated into the various levels of complexity of the health system. Although, historically, progress has been made in the construction of different forms of IESC in the SUS, in practice there are many difficulties related to its operationalization. In PHC, these obstacles are compounded by a set of changes that have great potential for changing the pillars that have been favoring institutional stability and the achievement of good health outcomes, above all, via the Family Health Strategy. With the historical underfunding of the SUS and its unfunding process by EC-95, the new funding model for the PHC, in a neo-focused and neo-selective way, for the poorest population, means to further restrict SUS resources. After carrying out a qualitative meta-synthesis of the challenges existing in the PHC practice scenarios described in the main studies that systematize these experiences in the country, it was up to us to present possible solutions to how the teaching scenarios in PHC will be reconfigured for the training of future health professionals in conditions that are so adverse to care, comprehensiveness, equity and with a real risk to interprofessionalism. In this sense, this product aims to reorient the organization of PHC services in order to minimize the impacts of neo-selectivity in care, service and health care.